Isolation of steroid CV-3 (C19H26O5) from Cyanotis vaga (Lour.) Schultes - Chua, Modesto T.; Santos, Alfredo C.; Abela, C.; Wagner, Ulrich (1982)
The acetone extract of Cyanotis vaga whole plant yielded a crystalline compound (C19H26O5) m.p. 248-251 C. Spectral data (IR, UV, NMR, MS and CD) are presented, showing the substance are an ecdysone, identical with the recently elucidated rubrosterone. This represents the second plant family reported to contain a steroid having an etiocholane skeleton.